2017
DOI: 10.1080/21688370.2017.1341969
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding proteins in the development and maintenance of the epidermal permeability barrier

Abstract: The skin of mammals and other terrestrial vertebrates protects the organism against the external environment, preventing heat, water and electrolyte loss, as well as entry of chemicals and pathogens. Impairments in the epidermal permeability barrier function are associated with the genesis and/or progression of a variety of pathological conditions, including genetic inflammatory diseases, microbial and viral infections, and photodamage induced by UV radiation. In mammals, the outside-in epidermal permeability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 141 publications
(193 reference statements)
0
11
0
Order By: Relevance
“…Adherens junctions are abundant in epithelial tissues. These junctions are composed of transmembrane proteins, such as E‐Cadherin, that mediate cell–cell contact (Crawford & Dagnino, ; Soares et al, ). Thus, the formation of adherens junctions can be assessed by detecting the presence of E‐Cadherin, which is indicative of epithelial barrier formation.…”
Section: Resultsmentioning
confidence: 99%
“…Adherens junctions are abundant in epithelial tissues. These junctions are composed of transmembrane proteins, such as E‐Cadherin, that mediate cell–cell contact (Crawford & Dagnino, ; Soares et al, ). Thus, the formation of adherens junctions can be assessed by detecting the presence of E‐Cadherin, which is indicative of epithelial barrier formation.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned before, increased occludin expression in activated γδ T cells enhancing the migration of γδ T cells from the epidermis to the lymph nodes, thus, upregulated occludin in CD8 + T cells from peripheral blood indicating that it may facilitate CD8 + T cells from blood migrating to the skin. Previous studies have shown that occludin plays an important role in the adhesion of lymphocytes to epithelial cells, as well as of exogenous occludin to Xenopus embryo cells in the form of self-ligands [ 12 , 30 , 31 ]. Therefore, we assumed that CD8 + T cells from PBMCs of vitiligo patients migrate to the skin, where occludin on the surface of CD8 + T cells may bind to the occludin on the surface of melanocytes to mediate the adhesion of CD8 + T cells and melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…TJ is involved in proliferation, differentiation, and adhesion in keratinocytes. The differentiation biomarkers filaggrin, involucrin, and integrin β1 are principal proteins in the construction of the skin-barrier property (Crawford and Dagnino, 2017). CoQ 0 could ameliorate the deficiency of filaggrin and integrin β1 but not involucrin in 1649b-treated HaCaT.…”
Section: Discussionmentioning
confidence: 99%